Implementation of Authentic Assessment among Social Studies Teachers in The Private Catholic Schools during Covid-19 Pandemic - Gorromeo, Ednalyn M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This research investigated the struggles faced by educators in implementing Authentic Assessment at Private Catholic Educa-tional Institutes within the Diocese of Iba during the 2022-2023 school year, specifically in the 3rd Quarter period. A descriptive research method using a survey questionnaire was employed to gather data from 101 Social Studies teachers. The findings indi-cated that the majority of respondents were female, single, col-lege-educated, and had been teaching for over five years. The respondents expressed confidence in their knowledge of imple-menting Authentic Assessment during the COVID-19 pandemic. Visual and kinesthetic methods were frequently used, with re-sponses indicating these were employed "often," while verbal and written methods were used "sometimes." The teachers disa-greed on the challenges they faced in implementing Authentic Assessment. No significant differences were found in the level of awareness on Authentic Assessment based on demographic var-iables such as sex, civil status, highest educational attainment, or years of teaching. However, there were significant differences in the frequency of using various assessment methods, particularly between visual, verbal, kinesthetic, and written methods. The study also highlighted significant differences in the challenges experienced based on the highest educational attainment. The researcher proposed an intervention program to address these challenges, recommending strategies such as improved report preparation, collaboration with parents and local government units, the provision of hands-on activities for students, and teacher workshops for mastery of assessment techniques. Fu-ture research is encouraged to replicate the study for a deeper and broader understanding of the challenges and practices relat-ed to Authentic Assessment.